Fundamentals of additive manufacturing for the practitioner : additive manufacturing skills in practice series - Kamara, Sheku; Faggiani, Kathy S. (Hoboken, NJ : Wiley, 2021)
"As the core book in Wiley's Additive Manufacturing Skills in Practice series, Fundamentals of Additive Manufacturing for the Practitioner provides an introduction to the methods and techniques needed to transition from traditional to additive manufacturing. The book opens by explaining how traditional manufacturing work roles change as industries move into additive manufacturing. Subsequent chapters follow the flow of the typical production process and explain topics such as additive manufacturing materials, processes, inputs, machine and build preparation, post-processing, and best practices. Case study examples in every chapter present common manufacturing issues or questions, then work through how to address them using additive manufacturing techniques. Each chapter also includes a problems/opportunities section that prompts readers to apply the chapter's techniques to their own work. Throughout the book, key options and decisions are highlighted to help practitioners understand how additive manufacturing changes existing workflows. Diagrams and tables are used liberally to present concepts in a visual way. Once readers master the book's content, they can use other titles in the Skills in Practice series to develop more advanced skills for specific industries and job functions"--
Introduction: Moving into Additive Manufacturing -- Is Additive Manufacturing the Right Solution? -- What Design and Inputs Does Additive Manufacturing Require? -- What Materials Does Additive Manufacturing Use? -- Which Additive Manufacturing Technology and Process Are Right for My Solution? -- What Machine and Build Preparation Occurs in Additive Manufacturing? -- What Occurs During the Additive Manufacturing Build Process? -- What Happens after the Additive Manufacturing Build Process Is Complete? -- What Do We Do to Move to Additive Manufacturing? -- Where Can I Learn More?
Includes index
Keywords: Additive manufacturing; Electronic books